Cancer chemoprevention via activation of proteostatic modules. (28th January 2018) - Sklirou, Aimilia; Papanagnou, Eleni-Dimitra; Fokialakis, Nikolas; Trougakos, Ioannis P.
Abstract: Proteins carry out the majority of cellular functions and maintain cellular homeodynamics mostly by participating in multimeric assemblies that operate as protein machines. Proteome quality control is thus critical for cellular functionality, and it is carried out through the curating activity of the proteostasis network (PN). Key components of the PN are the protein synthesis and trafficking modules, the endoplasmic reticulum unfolded protein response, molecular chaperones, and the two main degradation machineries, namely the ubiquitin proteasome and autophagy lysosome pathways. Part of the PN are also several stress responsive pathways, including nuclear factor erythroid 2-related factor 2 (Nrf2), which mobilises genomic responses against oxidative and/or xenobiotic damage. Nevertheless, the gradual accumulation of stressors during ageing or earlier due to lifestyle results in an increasingly damaged and unstable proteome. This outcome may then increase genomic instability due to reduced DNA replication fidelity or repair, leading to various age-related diseases such as cancer. Considering that the activation of proteostatic modules exerts anti-ageing effects in model organisms, we present herein a synopsis of studies showing that proteostatic modules activation (e.g. by natural products) represents a promising tumour-chemopreventive approach. Highlights: Proteome stability is ensured by the highly integrated modular proteostasis network. Activation of proteostatic modules delays age-related proteome dysfunction. Increased proteotoxic stress and proteome instability is a hallmark of cancer. The issue of how loss-of-proteostasis affects tumour formation remains elusive. By activating proteostatic modules natural products promote cancer chemoprevention.